Morphology and anatomy of larval development in black neon tetra fish Hyphessobrycon herbertaxelrodi (Characiformes: Characidae) - Çelik, Pınar (2026)
Introduction: The black neon tetra (Hyphessobrycon herbertaxelrodi) is a popular ornamental fish, and understanding its larval development is crucial for aquaculture practices. Objective: To examine the developmental stages during the larval period of black neon tetra produced under laboratory conditions. Methods: Larvae were sampled daily from hatching until reaching the juvenile stage. Each specimen was photographed and prepared for anatomical observations. Results: Morphological observations indicated that the mean total length (TL) of the larvae was 2.77 ± 0.08 mm on the first day after hatching (DAH) and increased to 12.26 ± 0.96 mm by the 29th-30th DAH when they reached the juvenile stage. Initially, the fins were in a primordial form, with the mouth and anus opening on the 4th and 6th DAH, respectively. The anal and dorsal fins began to differentiate on the 10th and 14th DAH, coinciding with the completion of notochord flexion on the 12th-13th DAH. The second swim bladder developed on the 14th and 15th DAH, and caudal fin bifurcation was observed on the 18th day. Anatomical observations indicated significant changes in the developmental process of black neon tetra larvae. On the 1st DAH, the digestive system of the yolk sac larva was in the shape of a flat long tube. By the early 3rd day, the mouth had opened, and the swim bladder had noticeably swollen, taking the form of a tube in the digestive canal. On the 5th day, the yolk sac had been depleted, and the stomach and intestine began to develop. By the 10th day, the liver had replaced the yolk sac, increasing the folds of the stomach and intestine. The juvenile stage commenced on the 29th-30th DAH, marking the end of the larval process. Conclusions: The findings provide essential insights into the morphological and developmental milestones of black neon tetra larvae, which are vital for enhancing aquaculture techniques and breeding protocols.